Study of dynamic behaviour of truck chassis - Zaman @ Bujang, Izzuddin (2005)
Tmck chassis is a major component in a vehicle system. It inte!:-Tfates the main component systems such as the suspension, engine, cab and trailer. Thus it often identified for refinement in order to develop vehicles with reduced cost and weight. Nowadays with the capabilities of advanced computer aided design and engineering tools, the process of chassis design in the automotive industry has been significantly refined. The application of FEA such as structural modification and optimization is used to reduce component complexity, weight and subsequently cost. Because the level of model complexity can be high, the opportunity for error can also be high. For this reason, some fonn of model verification is needed before design decisions made in the FEA environment can be implemented in production with high confidence. This thesis project describes the application of dynamic correlation techniques for verification of the FEA models of truck chassis. The dynamic characteristic of tmck chassis such as the natural frequency and mode shape will be detenllined using finite element method. Experimental measurement has been carried out to validate the analytically derived dynamic models. Modal testing is one of the methods that apply the experimental technique in detennining the modes of vibration. Initial results from both analysis show that the truck chassis experienced I >1 torsion mode for I >t natural frequency, 1 SI bending mode for 2nd natural frequency, 2nd torsion mode for 3 rd natural fi"equency and 2nd bending mode for 4th natural frequency. However there is a small discrepancy in tenns of frequency. Thus. the model updating of tTIlck chassis model has been carried by adjusting the selective properties such as Modulus Young and Poisson ratio in order to get better a!:-Tfeement in the natural frequency between both analysis. Finally. the modifications of the updated FE tTIlck chassis model has been suggested such as by consider adding the stiffener. The purpose is to reduce the vibration as well as to improve the strength of the tTIlck chassis.